Penguatan Kesiapsiagaan Kebakaran Melalui Sistem Peringatan Dini Berbasis Sensor dan Edukasi Mitigasi di Kantor Kecamatan Pancalang - Windarto Windarto; Taqwa Putra Budi Purnomo Sidi Hiram; Justin Bongsoikrama (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aimed to implement a sensor-based fire early warning system and strengthen the preparedness of staff at Pancalang District Office, Kuningan Regency, through fire mitigation education. The program applied a participatory Community Development approach supported by appropriate technology. Its stages included partner coordination, needs assessment, identification of installation points, system design, device installation, functional testing, mitigation education, emergency drill simulation, training on system operation and maintenance, and joint evaluation with the partner. The results showed that the sensor-based early warning system was successfully installed in a strategic area of the district office and was able to support initial fire detection through sensor responses, alarms, and warning indicators. The applied science and technology design demonstrated the integration of smoke or flame sensors, a microcontroller, and warning outputs, enabling staff to recognize potential hazards more quickly. The education and simulation activities improved staff understanding of fire risks, prevention measures, safety procedures, coordination flow, and initial actions when the alarm is activated. Maintenance training also provided the partner with basic skills to sustain the system after the program..